(untitled) (World Bulletin of Management and Law, 2024)
This article provides brief information on the application of methods for extracting hydrocarbons from gas and gas condensate fields, specific methods for applying methods for increasing gas condensate and gas yield, taking into account reservoir properties in the late stage of development